The Association of Depression and the Cardiovascular Risk Factors of Blood Pressure, HbA1c, and Body Mass Index among Patients with Diabetes: Results from the Translating Research into Action for Diabetes Study - Lindsay B. Kimbro; W. Neil Steers; Carol M. Mangione; O. Kenrik Duru; Susan L. Ettner (International Journal of Endocrinology)
Diabetic patients are nearly three times as likely to have depression as their nondiabetic counterparts. Patients with diabetes are already at risk for poor cardiovascular health. Using cross-sectional data from the translating research into action for diabetes (TRIAD) study, the authors tested the association of depression with cardiovascular risk factors in diabetic patients. Depression was measured using the patient health questionnaire (PHQ8). Patients who scored greater than 9 on the PHQ8 were classified as depressed and were compared with those who were not depressed (n=2,341). Depressed patients did not have significantly different blood pressure levels than those who were not depressed. However, those who were depressed had higher HbA1c levels than those who were not depressed (P<0.01) and higher BMIs than those who were not depressed (P<0.01). These results indicate that depressed diabetic patients are at greater risk of having poor control of cardiovascular risk factors and suggest that depression screening should be a standard practice among this patient group.